Pengaruh perencanaan pajak, beban pajak tangguhan, dan leverage terhadap praktik manajemen laba - Yogi Saputra (JURNAL EKOBIS DEWANTARA, 2018)
Abstrak The purpose of this study is to determine whether the tax planning, deferred tax burden and leverage to Practice Management Profit in Manufacturing Companies either partially or simultaneously. Data obtained from Annual Report and Financial Report published in Indonesia Stock Exchange which then can be processed. In this study, earnings management is measured by calculating Discretionary Accruals. Tax planning is measured using TRR (Tax Retention Rate), deferred tax expense is measured by total deferred tax expense divided by total assets and leverage measured by debt divided by total assets. The study population consisted of 15 manufacturing companies sub-sector consumer goods and observation period starting in 2012 - 2016. The data used in the study is secondary data and sample selection by purposive sampling method that meets the criteria of the sample. The analytical method used is multiple linear analyst method to test the effect of tax planning, deferred tax burden and leverage to earnings management. Based on the results of hypothesis testing using multiple linear analysis method in this study, it can be concluded partially that the tax planning does not significantly influence earnings management while the deferred tax burden and leverage have a significant effect on earnings management. .